Beta Testing in Social Work. (March 2017) - Traube, Dorian E.; Begun, Stephanie; Petering, Robin; Flynn, Marilyn L.
The field of social work does not currently have a widely adopted method for expediting innovations into micro- or macropractice. Although it is common in fields such as engineering and business to have formal processes for accelerating scientific advances into consumer markets, few comparable mechanisms exist in the social sciences or social services. Given that beta testing is successfully used to scale innovation in business and engineering, why is there no method for beta testing in social work? Could this be the reason that innovations in social work practice remain decades behind scientific research findings? This article explores reasons for the scarcity of options for scaling innovation in the field of social work and proposes a method for shortening development cycles for social work innovations to ensure that advances reach consumers—and ultimately improve their lives—more quickly.